\(A=\left|2x-\frac{1}{3}\right|-1\frac{3}{4}\)
Có: \(\left|2x-\frac{1}{3}\right|\ge0\text{ với mọi }x\)
\(\Rightarrow\left|2x-\frac{1}{3}\right|-1\frac{3}{4}\ge-1\frac{3}{4}\text{ với mọi }x\)
\(\Rightarrow A\ge-1\frac{3}{4}\text{ với mọi }x\)
Vậy GTNN của \(A=-1\frac{3}{4}\)
Dấu '"=" xảy ra khi \(\left|2x-\frac{1}{3}\right|=0\\ \Leftrightarrow2x-\frac{1}{3}=0\\ \Leftrightarrow2x=\frac{1}{3}\\ \Leftrightarrow x=\frac{1}{6}\)
________________________________________________
\(B=\frac{1}{3}\left|x-2\right|+2\left|3-\frac{1}{2}y\right|+4\)
Có: \(\left\{{}\begin{matrix}\frac{1}{3}\left|x-2\right|\ge0\text{ với mọi }x\\2\left|3-\frac{1}{2}y\right|\ge0\text{ với mọi }y\end{matrix}\right.\)
\(\Rightarrow\frac{1}{3}\left|x-2\right|+2\left|3-\frac{1}{2}y\right|\ge0\text{ với mọi }x;y\\ \Rightarrow\frac{1}{3}\left|x-2\right|+2\left|3-\frac{1}{2}y\right|+4\ge4\text{ với mọi }x;y\\ \Rightarrow B\ge4\text{ với mọi }x;y\)
Vậy GTNN của B = 4
Dấu "=" xảy ra khi \(\left\{{}\begin{matrix}\frac{1}{3}\left|x-2\right|=0\\2\left|3-\frac{1}{2}y\right|=0\end{matrix}\right.\\ \Leftrightarrow\left\{{}\begin{matrix}\left|x-2\right|=0\\\left|3-\frac{1}{2}y\right|=0\end{matrix}\right.\\ \Leftrightarrow\left\{{}\begin{matrix}x-2=0\\3-\frac{1}{2}y=0\end{matrix}\right.\\ \Leftrightarrow\left\{{}\begin{matrix}x=2\\\frac{1}{2}y=3\end{matrix}\right.\\ \Leftrightarrow\left\{{}\begin{matrix}x=2\\y=6\end{matrix}\right.\)
làm đại:((,sai thì thông cảm nha :))
khúc cuối sai sai tý kkk
\(A=\left|2x-\frac{1}{3}\right|-1\frac{3}{4}=\left|2x-\frac{1}{3}\right|+\left(-\frac{7}{4}\right)\)
+Có: \(\left|2x-\frac{1}{3}\right|\ge0với\forall x\\ \Rightarrow\left|2x-\frac{1}{3}\right|+\left(-\frac{7}{4}\right)\ge-\frac{7}{4}\\ \Leftrightarrow A\ge-\frac{7}{4}\)
+Dấu ''='' xảy ra khi \(\left|2x-\frac{1}{3}\right|=0\Leftrightarrow x=\frac{1}{6}\)
+Vậy \(A_{min}=-\frac{7}{4}\) khi \(x=\frac{1}{6}\)
\(B=\frac{1}{3}\left|x-2\right|+2\left|3-\frac{1}{2}y\right|+4\)
+Có: \(\left|x-2\right|\ge0với\forall x\\ \left|3-\frac{1}{2}y\right|\ge0với\forall x\\ \Rightarrow\frac{1}{3}\left|x-2\right|+2\left|3-\frac{1}{2}y\right|+4\ge4\\ \Leftrightarrow B\ge4\)
+Dấu ''='' xảy ra khi \(\left|x-2\right|=0\Leftrightarrow x=2;\left|3-\frac{1}{2}y\right|=0\Leftrightarrow y=6\)
+Vậy \(B_{min}=4\) khi \(x=2;\left|3-\frac{1}{2}y\right|=0\Leftrightarrow y=6\)